High-gloss ASA rubber powder and preparation method thereof

CN119119384APending Publication Date: 2024-12-13BINZHOU YONGHONG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411377893.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

Smart Images

  • Figure BDA0005069143020000171
    Figure BDA0005069143020000171
  • Figure BDA0005069143020000181
    Figure BDA0005069143020000181
Patent Text Reader

Abstract

The invention provides high-gloss ASA rubber powder and a preparation method thereof, and relates to the technical field of high polymer material processing. The high-gloss ASA rubber powder is a grafted copolymer of acrylate rubber and a styrene-acrylonitrile copolymer, and comprises a core layer, a core layer and a shell layer from inside to outside, the particle size of the core layer is 50 to 100 nm; the particle size of the high-gloss ASA rubber powder is 100 to 300 nm; the core layer is prepared from the following raw material components in parts by mass: 100 to 120 parts of butyl acrylate; 1 to 5 parts of methyl propanamide; 1-10 parts of a composite emulsifier; 0.1 to 1 part of an initiator; 0.5 to 1.2 parts of nano silicon dioxide; and 100 to 180 parts of water. By optimizing the monomer components and proportion and optimizing the preparation method, the glossiness of the ASA colloidal particles is remarkably improved while the weather resistance, heat resistance and impact strength of the ASA colloidal particles are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material processing, and in particular to high-gloss ASA rubber powder and a preparation method thereof. Background Art

[0002] ASA rubber powder is a ternary polymer composed of acrylate (A), styrene (S), and acrylonitrile (A). ASA rubber powder is a typical core-shell impact modifier, in which the core is an acrylic rubber and the shell is a grafted copolymer of styrene and acrylonitrile. The performance of ASA rubber powder is similar to that of ABS rubber powder. Both have good mechanical properties, processing properties, electrical insulation properties, chemical resistance, and coloring properties. However, since ASA rubber powder introduces acrylic rubber without double bonds, the weather resistance of ASA rubber powder is much higher than that of ABS rubber powder. ASA rubber powder can not only be used as a toughening modifier to modify thermoplastics such as polyvinyl chloride, polycarbonate, and nylon, but can also be blended with styrene-acrylonitrile copolymers to make ASA engineering resins, which are widely used in the fields of automobiles, electronic appliances, outdoor building materials, etc.

[0003] Chinese patent CN 113150460 A discloses a method for preparing ASA resin. In the synthesis of ASA graft copolymer, diene monomers are used to replace traditional crosslinking agents and grafting agents. While improving the crosslinking degree and grafting efficiency of ASA resin, the glass transition temperature of polyacrylate copolymer is reduced, thereby comprehensively improving various properties of ASA resin. The impact strength of ASA resin after the improved process is greater than 10KJ / m 2 , reaching the level of imported ASA resin. However, it is not enough for ASA resin to have only high impact strength, it must also have good gloss.

[0004] The ASA resin provided by Chinese patent CN 109897141 B has raw materials for preparation including main materials, initiators and molecular weight regulators; in terms of mass percentage, the main materials include the following components: 6-30% acrylic rubber, 10-40% ASA polymerization solvent, 30-55% styrene, and 10-25% acrylonitrile; the mass of the initiator is 0.01-0.1% of the total mass of the acrylic rubber, styrene and acrylonitrile; the mass of the molecular weight regulator is 0.01-0.8% of the total mass of the acrylic rubber, styrene and acrylonitrile. The above ASA resin is prepared by bulk polymerization, which is simple and has no impurities such as emulsifiers brought in by emulsion polymerization, thus overcoming the problem of large amounts of wastewater generated by emulsion polymerization of ASA. However, on the one hand, it is difficult to control the particle size by bulk polymerization, and on the other hand, the glossiness of the obtained ASA resin is not good, which makes it difficult to meet the needs of industries such as automotive accessories.

[0005] The core of ASA resin lies in the preparation of ASA high-rubber powder. Its technical bottleneck is mainly the core-shell structure, particle size control and the dispersion, wetting and compatibility of its matrix plastic. It is a systematic research and development and production project. At present, the preparation methods of ASA resin powder mainly include: emulsion blending method and grafting method. At present, the grafting method is mainly used for preparation, and the grafting method is divided into bulk polymerization method, suspension polymerization method and emulsion polymerization method. Bulk polymerization and suspension polymerization are difficult to obtain high-quality products because the rubber particle size is not easy to control. The emulsion grafting polymerization method is conducive to controlling the reaction rate and the distribution of particle size. The emulsion grafting polymerization method can also be divided into one-step polymerization method and multi-step polymerization method. Since the one-step polymerization method is difficult to control the reaction rate, the number of latex particles in the obtained emulsion increases, the particle size decreases, and the surface area of ​​the latex particles also increases, making it difficult for the shell layer to cover it, so that the impact strength, colorability and fluidity of the ASA resin powder are reduced, and it cannot meet user needs. Based on this, researchers in this field have been committed to developing ASA rubber powder and its preparation process, and are committed to controlling its particle size and structure to improve its performance.

[0006] However, some ASA resins used in the fields of automobiles, electronic products, etc. are not only not good enough in terms of weather resistance, but also need good gloss and impact resistance. Existing ASA particles cannot improve the gloss of the resin while taking into account the impact resistance of the material, which limits its application in the fields of automobiles, electronic products, etc. Therefore, finding an ASA resin material with both good impact and gloss has become an urgent problem to be solved in the industry. Summary of the invention

[0007] In view of the above problems, the present invention provides a high-gloss ASA rubber powder and a preparation method thereof. The ASA rubber powder comprises a three-layer structure of a core layer, a nucleus layer and a shell layer from the inside to the outside. By optimizing monomer components and ratios, controlling particle size, etc., the prepared ASA rubber powder not only has good impact strength and heat resistance, but also significantly improves gloss.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] On the one hand, the present invention provides a high-gloss ASA rubber powder, which is a graft copolymer of acrylic rubber and styrene-acrylonitrile copolymer, and comprises a core layer, a core layer and a shell layer from the inside to the outside; the particle size of the core layer is 50-100nm; the particle size of the high-gloss ASA rubber powder is 100-300nm;

[0010] The core layer comprises the following components in terms of weight:

[0011] Butyl acrylate 100-120 parts;

[0012] 1-5 parts of methylpropionamide;

[0013] 1-10 parts of composite emulsifier;

[0014] 1-10 parts of initiator;

[0015] Nano silicon dioxide 0.5-1.2 parts;

[0016] 100-180 parts of water.

[0017] Preferably, the particle size of the core layer is 60-80 nm; the particle size of the high-gloss ASA rubber powder is 220-240 nm.

[0018] Preferably, the molecular weight of the high gloss ASA rubber powder is 400,000-600,000.

[0019] Preferably, the core layer comprises the following components in terms of weight:

[0020] Butyl acrylate 90-120 parts;

[0021] 2.5-5 parts of methylpropionamide;

[0022] 4-10 parts of composite emulsifier;

[0023] 5-10 parts of initiator;

[0024] Nano silicon dioxide 0.8-1.2 parts;

[0025] 150-180 parts of water.

[0026] Further preferably, the raw materials of the core layer include the following components in parts by mass:

[0027] 100 parts of butyl acrylate;

[0028] 4 parts of methylpropionamide;

[0029] 6 parts of composite emulsifier;

[0030] Initiator 8 parts;

[0031] 1.2 parts of nano silicon dioxide;

[0032] 180 parts of water.

[0033] Preferably, the composite emulsifier comprises sodium allyl ether hydroxypropane sulfonate, sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, fatty acid amide and potassium bicarbonate.

[0034] Preferably, in the composite emulsifier, the mass ratio of sodium allyl ether hydroxypropane sulfonate to sodium 2-propyl ether 3-hydroxypropane-1-sulfonate is 1:0.4-0.8; further preferably, the mass ratio of sodium allyl ether hydroxypropane sulfonate to sodium 2-propyl ether 3-hydroxypropane-1-sulfonate is 1:0.5-0.6.

[0035] Preferably, the composite emulsifier comprises the following components by weight: 10-20 parts of sodium allyl ether hydroxypropane sulfonate, 10-14 parts of sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, 1-2 parts of fatty acid amide and 6-8 parts of potassium bicarbonate.

[0036] Further preferably, the composite emulsifier comprises the following components, calculated by mass: 18 parts of sodium allyl ether hydroxypropane sulfonate, 10.8 parts of sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, 1.2 parts of fatty acid amide and 6 parts of potassium bicarbonate.

[0037] Preferably, the preparation method of the composite emulsifier is: dissolving sodium allyl ether hydroxypropane sulfonate and sodium 2-propyl ether 3-hydroxypropane-1-sulfonate in water, and mixing at 20-30° C. for 20-30 minutes; adding fatty acid amide and potassium bicarbonate, and continuing mixing for 10-15 minutes to obtain the composite emulsifier.

[0038] Preferably, the initiator is at least one of persulfate, thiosulfate and bisulfite;

[0039] Further preferably, the initiator is persulfate;

[0040] More preferably, the initiator is ammonium persulfate and potassium persulfate.

[0041] Preferably, the mass ratio of the ammonium persulfate to the potassium persulfate is 1:1-1.2; further preferably, the mass ratio of the ammonium persulfate to the potassium persulfate is 1:1.

[0042] Preferably, the raw materials of the core layer include the following components by mass fraction:

[0043] Styrene 15-25 parts;

[0044] 4-10 parts of acrylonitrile;

[0045] Composite emulsifier 0.1-1.5 parts;

[0046] Ethoxy trimethylolpropane triacrylate 0.5-1.2 parts;

[0047] Initiator 0.1-0.3 parts;

[0048] Molecular weight regulator 0.05-0.15 parts;

[0049] 20-40 parts water;

[0050] Further preferably, the raw materials of the core layer include the following components by mass fraction:

[0051] Styrene 20-25 parts;

[0052] Acrylonitrile 5-10 parts;

[0053] Composite emulsifier 0.8-1.2 parts;

[0054] Ethoxy trimethylolpropane triacrylate 0.5-0.8 parts;

[0055] Initiator 0.1-0.2 parts;

[0056] Molecular weight regulator 0.05-0.08 parts;

[0057] 30-40 parts water;

[0058] More preferably, the raw materials of the core layer include the following components by mass fraction:

[0059] Styrene 21 parts;

[0060] 6 parts of acrylonitrile;

[0061] 1.2 parts of composite emulsifier;

[0062] 0.6 parts of ethoxy trimethylolpropane triacrylate;

[0063] Initiator 0.2 parts;

[0064] 0.06 parts of molecular weight regulator;

[0065] 38 parts water;

[0066] Preferably, the molecular weight regulator is diisopropyl xanthate disulfide and n-dodecyl;

[0067] Preferably, the mass ratio of diisopropyl xanthate disulfide to n-dodecyl is 0.1-0.5:1; further preferably, the mass ratio of diisopropyl xanthate disulfide to n-dodecyl is 0.2:1.

[0068] Preferably, the shell layer, the raw materials, by mass fraction, comprise the following components:

[0069] 40-60 parts of styrene;

[0070] 32-45 parts of acrylonitrile;

[0071] 2-5 parts of methyl methacrylate;

[0072] Composite emulsifier 0.2-2 parts;

[0073] Initiator 0.2-1 part;

[0074] 40-100 parts of water;

[0075] Further preferably, the shell layer, the raw materials, by mass fraction, comprise the following components:

[0076] 40-50 parts of styrene;

[0077] 32-40 parts of acrylonitrile;

[0078] 3-5 parts of methyl methacrylate;

[0079] Composite emulsifier 0.8-2 parts;

[0080] Initiator 0.2-0.8 parts;

[0081] 60-100 parts of water;

[0082] More preferably, the shell layer, the raw materials, by mass fraction, comprise the following components:

[0083] 45 parts of styrene;

[0084] 38 parts of acrylonitrile;

[0085] 4 parts of methyl methacrylate;

[0086] 1.2 parts of composite emulsifier;

[0087] 0.4 parts of initiator;

[0088] 80 parts water;

[0089] Preferably, the mass ratio of the core layer: the core layer: the shell layer is 25-40: 30-35: 30-40; further preferably, the mass ratio of the core layer: the core layer: the shell layer is 32: 34: 38.

[0090] On the other hand, the present invention provides a method for preparing the above-mentioned high gloss ASA rubber powder, comprising the following steps:

[0091] S1: mixing butyl acrylate, methyl propionamide, composite emulsifier, initiator, nano-silica and water, and polymerizing to obtain a core layer emulsion;

[0092] S2: the core layer emulsion is mixed with styrene, acrylonitrile, composite emulsifier, ethoxy trimethylol propane triacrylate, molecular weight regulator and water, and an initiator is added for polymerization to obtain a double-layer structure of a core layer wrapped in a core layer;

[0093] S3: The double-layer structure of the core layer wrapped in the core layer obtained in S2 is mixed with styrene, acrylonitrile, methyl methacrylate, a composite emulsifier and water, and an initiator is added for polymerization, condensation, aging, dehydration and drying.

[0094] Preferably, in S1, the polymerization temperature is 55-65°C;

[0095] Preferably, in S2, the polymerization temperature is 60-80°C;

[0096] Preferably, in S3, the polymerization temperature is 80-90°C.

[0097] Compared with the prior art, the present invention has the following beneficial effects:

[0098] 1. The ASA rubber powder provided by the present invention has a three-layer structure, which includes a core layer, a nucleus layer and a shell layer from the inside to the outside. When preparing the core layer, nano-silicon dioxide is added, the composite emulsifier and the proportion of each component are optimized, and the particle size is controlled, which ensures the compatibility of the material on the one hand and makes the material have higher gloss on the other hand; when preparing the core layer, the components are optimized and the molecular weight is controlled, which significantly improves the gloss of the ASA rubber particles while ensuring the weather resistance, heat resistance and impact strength of the ASA rubber particles; and the particle size of the ASA rubber powder is further controlled by the shell layer, which significantly improves the gloss of the ASA rubber particles while ensuring the weather resistance, heat resistance and impact strength of the ASA rubber particles.

[0099] 2. The present invention optimizes the monomer components and ratios and the preparation method, thereby significantly improving the glossiness of the ASA particles while ensuring their weather resistance, heat resistance and impact strength. DETAILED DESCRIPTION

[0100] In order to make the technical means, creative features, purpose and effect of the present invention easy to understand, the present invention is further explained below in conjunction with specific embodiments, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without making creative work all belong to the protection scope of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited. The technology and scientific terms used in the embodiments have the meanings commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0101] Example 1

[0102] A high-gloss ASA rubber powder is a graft copolymer of acrylic rubber and styrene-acrylonitrile copolymer, which comprises a core layer, a nucleus layer and a shell layer from the inside to the outside;

[0103] Its formula is:

[0104] The core layer, raw materials by weight, include the following components:

[0105] 100 parts of butyl acrylate;

[0106] 4 parts of methylpropionamide;

[0107] 6 parts of composite emulsifier;

[0108] 4 parts of ammonium persulfate;

[0109] 4 parts of potassium persulfate;

[0110] 1.2 parts of nano silicon dioxide;

[0111] 180 parts of deionized water.

[0112] The core layer, raw materials by mass fraction, includes the following components:

[0113] Styrene 21 parts;

[0114] 6 parts of acrylonitrile;

[0115] 1.2 parts of composite emulsifier;

[0116] 0.6 parts of ethoxy trimethylolpropane triacrylate;

[0117] 0.09 parts of ammonium persulfate;

[0118] Potassium persulfate 0.11 parts;

[0119] 0.01 parts of diisopropyl xanthate disulfide;

[0120] 0.05 parts of n-dodecyl;

[0121] 38 parts of deionized water.

[0122] Shell layer, raw materials by mass fraction, including the following components:

[0123] 45 parts of styrene;

[0124] 38 parts of acrylonitrile;

[0125] 4 parts of methyl methacrylate;

[0126] 1.2 parts of composite emulsifier;

[0127] 0.2 parts of ammonium persulfate;

[0128] 0.2 parts of potassium persulfate;

[0129] 80 parts of deionized water;

[0130] The composite emulsifier described above comprises the following components by mass fraction:

[0131] 18 parts of sodium allyl ether hydroxypropane sulfonate, 10.8 parts of sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, 1.2 parts of fatty acid amide and 6 parts of potassium bicarbonate.

[0132] The preparation method of the above-mentioned composite emulsifier is:

[0133] Sodium allyl ether hydroxypropane sulfonate and sodium 2-propyl ether 3-hydroxypropane-1-sulfonate were dissolved in deionized water and mixed at 20° C. for 25 minutes; fatty acid amide and potassium bicarbonate were added and mixed for 15 minutes to obtain a composite emulsifier.

[0134] The mass ratio of the core layer: the core layer: the shell layer is 32:34:38.

[0135] The method for preparing the high gloss ASA rubber powder comprises the following steps:

[0136] S1: mixing butyl acrylate, methyl propionamide, composite emulsifier, initiator, nano-silica and deionized water, and polymerizing at 60°C to obtain a core layer emulsion;

[0137] S2: the core layer emulsion is mixed with styrene, acrylonitrile, composite emulsifier, ethoxy trimethylol propane triacrylate, molecular weight regulator and deionized water, an initiator is added, and polymerization is carried out at 65°C to obtain a double-layer structure in which the core layer is wrapped by the core layer;

[0138] S3: The double-layer structure of the core layer wrapped in the core layer obtained in S2 is mixed with styrene, acrylonitrile, methyl methacrylate, a composite emulsifier and deionized water, an initiator is added, and polymerization is carried out at 85° C., condensation, aging, dehydration and drying.

[0139] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0140] Example 2

[0141] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0142] The core layer, raw materials by weight, include the following components:

[0143] Butyl acrylate 120 parts;

[0144] 1 part of methylpropionamide;

[0145] 10 parts of composite emulsifier;

[0146] 3 parts of ammonium persulfate;

[0147] Potassium persulfate 3 parts;

[0148] 0.5 parts of nano silicon dioxide;

[0149] 150 parts of deionized water.

[0150] The core layer, raw materials by mass fraction, includes the following components:

[0151] Styrene 15 parts;

[0152] 10 parts of acrylonitrile;

[0153] 0.4 parts of composite emulsifier;

[0154] 1.2 parts of ethoxy trimethylolpropane triacrylate;

[0155] 0.045 parts of ammonium persulfate;

[0156] Potassium persulfate 0.055 parts;

[0157] 0.025 parts of diisopropyl xanthate disulfide;

[0158] 0.125 parts of n-dodecyl;

[0159] 22 parts of deionized water.

[0160] Shell layer, raw materials by mass fraction, including the following components:

[0161] 60 parts of styrene;

[0162] 45 parts of acrylonitrile;

[0163] 2 parts of methyl methacrylate;

[0164] 0.2 parts of composite emulsifier;

[0165] 0.1 part of ammonium persulfate;

[0166] Potassium persulfate 0.1 part;

[0167] 45 parts of deionized water;

[0168] The composite emulsifier described above comprises the following components by mass fraction:

[0169] 12 parts of sodium allyl ether hydroxypropane sulfonate, 7.2 parts of sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, 2 parts of fatty acid amide and 8 parts of potassium bicarbonate.

[0170] The mass ratio of the core layer: the core layer: the shell layer is 25:30:40.

[0171] The rest is the same as Example 1.

[0172] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0173] Example 3

[0174] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0175] The core layer, raw materials by weight, include the following components:

[0176] 110 parts of butyl acrylate;

[0177] 5 parts of methylpropionamide;

[0178] 2 parts of composite emulsifier;

[0179] 1 part of ammonium persulfate;

[0180] 1 part potassium persulfate;

[0181] 1.2 parts of nano silicon dioxide;

[0182] 180 parts of deionized water.

[0183] The core layer, raw materials by mass fraction, includes the following components:

[0184] Styrene 25 parts;

[0185] 8 parts of acrylonitrile;

[0186] 0.8 part of composite emulsifier;

[0187] 0.5 parts of ethoxy trimethylolpropane triacrylate;

[0188] 0.14 parts of ammonium persulfate;

[0189] Potassium persulfate 0.16 parts;

[0190] 0.033 parts of diisopropyl xanthate disulfide;

[0191] 0.067 parts of n-dodecyl;

[0192] 36 parts of deionized water.

[0193] Shell layer, raw materials by mass fraction, including the following components:

[0194] 40 parts of styrene;

[0195] 32 parts of acrylonitrile;

[0196] 5 parts of methyl methacrylate;

[0197] 2 parts of composite emulsifier;

[0198] 0.5 parts of ammonium persulfate;

[0199] 0.5 parts of potassium persulfate;

[0200] 100 parts of deionized water;

[0201] The composite emulsifier described above comprises the following components by mass fraction:

[0202] 20 parts of sodium allyl ether hydroxypropane sulfonate, 10 parts of sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, 1 part of fatty acid amide and 7 parts of potassium bicarbonate.

[0203] The mass ratio of the core layer: the core layer: the shell layer is 40:35:38.

[0204] The rest is the same as Example 1.

[0205] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0206] Comparative Example 1

[0207] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0208] The core layer, raw materials by weight, include the following components:

[0209] Butyl acrylate 150 parts;

[0210] 6 parts of methylpropionamide;

[0211] 15 parts of composite emulsifier;

[0212] 8 parts of ammonium persulfate;

[0213] Potassium persulfate 8 parts;

[0214] 1.5 parts of nano silicon dioxide;

[0215] 190 parts of deionized water.

[0216] The core layer, raw materials by mass fraction, includes the following components:

[0217] 30 parts of styrene;

[0218] 3 parts of acrylonitrile;

[0219] 2 parts of composite emulsifier;

[0220] 2 parts of ethoxy trimethylolpropane triacrylate;

[0221] 1 part of ammonium persulfate;

[0222] Potassium persulfate 5 parts;

[0223] 0.5 parts of diisopropyl xanthate disulfide;

[0224] 1 part of n-dodecyl;

[0225] 100 parts of deionized water.

[0226] Shell layer, raw materials by mass fraction, including the following components:

[0227] 65 parts of styrene;

[0228] 65 parts of acrylonitrile;

[0229] 8 parts of methyl methacrylate;

[0230] 0.5 part of composite emulsifier;

[0231] 0.1 part of ammonium persulfate;

[0232] 1.8 parts of potassium persulfate;

[0233] 150 parts of deionized water;

[0234] The rest is the same as Example 1.

[0235] The particle size of the core layer is 120-200nm; the particle size of the high-gloss ASA rubber powder is 350-500nm; and the molecular weight of the high-gloss ASA rubber powder is 500,000-800,000.

[0236] Comparative Example 2

[0237] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: the core layer, the raw materials are calculated by weight, and include the following components:

[0238] Butyl acrylate 80 parts;

[0239] 0.5 part of methylpropionamide;

[0240] 12 parts of composite emulsifier;

[0241] 0.4 parts of ammonium persulfate;

[0242] 0.4 parts of potassium persulfate;

[0243] 0.4 parts of nano silicon dioxide;

[0244] 80 parts of deionized water.

[0245] The core layer, raw materials by mass fraction, includes the following components:

[0246] Styrene 14 parts;

[0247] 14 parts of acrylonitrile;

[0248] 2.5 parts of composite emulsifier;

[0249] 2.4 parts of ethoxy trimethylolpropane triacrylate;

[0250] 0.3 parts of ammonium persulfate;

[0251] 0.3 parts of potassium persulfate;

[0252] 0.1 part of diisopropyl xanthate disulfide;

[0253] 0.1 part of n-dodecyl;

[0254] 50 parts of deionized water.

[0255] Shell layer, raw materials by mass fraction, including the following components:

[0256] 30 parts of styrene;

[0257] 30 parts of acrylonitrile;

[0258] 1 part of methyl methacrylate;

[0259] 0.1 part of composite emulsifier;

[0260] 0.05 parts of ammonium persulfate;

[0261] Potassium persulfate 0.05 parts;

[0262] 50 parts of deionized water;

[0263] The rest is the same as Example 1.

[0264] The particle size of the core layer is 30-100nm; the particle size of the high-gloss ASA rubber powder is 150-200nm; and the molecular weight of the high-gloss ASA rubber powder is 200,000-300,000.

[0265] Comparative Example 3

[0266] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0267] The core layer, raw materials by weight, include the following components:

[0268] 100 parts of butyl acrylate;

[0269] 4 parts of methylpropionamide;

[0270] 6 parts of composite emulsifier;

[0271] 4 parts of ammonium persulfate;

[0272] Potassium persulfate 4 parts;

[0273] 181.2 parts of deionized water.

[0274] The rest is the same as Example 1.

[0275] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0276] Comparative Example 4

[0277] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0278] The core layer, raw materials by weight, include the following components:

[0279] 100 parts of butyl acrylate;

[0280] 4 parts of methylpropionamide;

[0281] 6 parts of composite emulsifier;

[0282] 4 parts of ammonium persulfate;

[0283] Potassium persulfate 4 parts;

[0284] SAM-020 1.2 parts;

[0285] 180 parts of deionized water.

[0286] The rest is the same as Example 1.

[0287] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0288] Comparative Example 5

[0289] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0290] The core layer, raw materials by mass fraction, includes the following components:

[0291] Styrene 21 parts;

[0292] 6 parts of acrylonitrile;

[0293] 1.2 parts of composite emulsifier;

[0294] Allyl methacrylate 0.6 part;

[0295] 0.09 parts of ammonium persulfate;

[0296] Potassium persulfate 0.11 parts;

[0297] 0.01 parts of diisopropyl xanthate disulfide;

[0298] 0.05 parts of n-dodecyl;

[0299] 38 parts of deionized water.

[0300] The rest is the same as Example 1.

[0301] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0302] Comparative Example 6

[0303] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0304] The core layer, raw materials by mass fraction, includes the following components:

[0305] Styrene 21 parts;

[0306] 6 parts of acrylonitrile;

[0307] 1.2 parts of composite emulsifier;

[0308] Allyl methacrylate 0.6 part;

[0309] 0.09 parts of ammonium persulfate;

[0310] Potassium persulfate 0.11 parts;

[0311] 0.06 parts of diisopropyl xanthate disulfide;

[0312] 38 parts of deionized water.

[0313] The rest is the same as Example 1.

[0314] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 500,000-800,000.

[0315] Comparative Example 7

[0316] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0317] The core layer, raw materials by mass fraction, includes the following components:

[0318] Styrene 21 parts;

[0319] 6 parts of acrylonitrile;

[0320] 1.2 parts of composite emulsifier;

[0321] Allyl methacrylate 0.6 part;

[0322] 0.09 parts of ammonium persulfate;

[0323] Potassium persulfate 0.11 parts;

[0324] 0.06 parts of n-dodecyl;

[0325] 38 parts of deionized water.

[0326] The rest is the same as Example 1.

[0327] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 500,000-700,000.

[0328] Comparative Example 8

[0329] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0330] Sodium lauryl sulfate was used instead of the composite emulsifier.

[0331] The rest is the same as Example 1.

[0332] The particle size of the core layer is 120-180nm; the particle size of the high-gloss ASA rubber powder is 300-450nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0333] Comparative Example 9

[0334] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0335] The composite emulsifier comprises the following components by mass fraction:

[0336] 8 parts of sodium allyl ether hydroxypropane sulfonate, 20 parts of sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, 0.8 parts of fatty acid amide and 10 parts of potassium bicarbonate.

[0337] The rest is the same as Example 1.

[0338] The particle size of the core layer is 120-200nm; the particle size of the high-gloss ASA rubber powder is 280-450nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0339] Comparative Example 10

[0340] A high gloss ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0341] The ammonium persulfate is replaced by potassium persulfate;

[0342] The rest is the same as Example 1.

[0343] The particle size of the core layer is 50-150nm; the particle size of the high-gloss ASA rubber powder is 200-350nm; and the molecular weight of the high-gloss ASA rubber powder is 400000-600000.

[0344] Comparative Example 11

[0345] A high gloss ASA rubber powder, compared with Example 1, only the mass ratio of the core layer: the core layer: the shell layer is different, specifically:

[0346] The mass ratio of the core layer: the core layer: the shell layer is 20:40:42.

[0347] The rest is the same as Example 1.

[0348] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0349] Comparative Example 12

[0350] A high gloss ASA rubber powder, compared with Example 1, only the mass ratio of the core layer: the core layer: the shell layer is different, specifically:

[0351] The mass ratio of the core layer: the core layer: the shell layer is 45:30:35.

[0352] The rest is the same as Example 1.

[0353] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0354] Comparative Example 13

[0355] A high gloss ASA rubber powder, compared with Example 1, only the preparation method is different:

[0356] The method for preparing the high gloss ASA rubber powder comprises the following steps:

[0357] S1: mixing butyl acrylate, methyl propionamide, composite emulsifier, initiator, nano-silica and deionized water, and polymerizing at 85°C to obtain a core layer emulsion;

[0358] S2: the core layer emulsion is mixed with styrene, acrylonitrile, composite emulsifier, ethoxy trimethylol propane triacrylate, molecular weight regulator and deionized water, an initiator is added, and polymerization is carried out at 50°C to obtain a double-layer structure in which the core layer is wrapped by the core layer;

[0359] S3: The double-layer structure of the core layer wrapped by the core layer obtained in S2 is mixed with styrene, acrylonitrile, methyl methacrylate, a composite emulsifier and deionized water, an initiator is added, and polymerization is performed at 100° C., condensation, aging, dehydration and drying.

[0360] The rest is the same as Example 1.

[0361] The particle size of the core layer is 60-80nm; the particle size of the high-gloss ASA rubber powder is 220-240nm; and the molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

[0362] Test Case

[0363] The high gloss ASA rubber powder prepared in Examples 1-3 of the present invention and Comparative Examples 1-13 was mixed with SAN resin in a mass ratio of 3:7, stirred at 1000 r / min for 15 min, and then added to a twin-screw extruder. After melting, extrusion, shaping, and drying, test samples were obtained and performance tests were performed.

[0364] Parameters of the twin-screw extruder: main engine speed: 160r / min, feeding speed: 55r / min, aspect ratio of the extruder: 36, reference temperatures of the four sections of screw heating: zone 1 temperature 180℃, zone 2 temperature 230℃, zone 3 temperature 230℃, zone 4 temperature 260℃, residence time 3min, pressure 18Mpa.

[0365] Gloss: Tested in accordance with GB / T8807-1988 "Test method for mirror gloss of plastics" and the test angle is 60°.

[0366] Notched impact strength: The notched impact strength of the sample is measured in accordance with GB / T1843-2008 "Determination of Izod Impact Strength of Plastics" at a temperature of 23°C.

[0367] Melt index: According to GB / T3682 "Test method for melt flow rate of thermoplastics", the melt index is measured using the melt flow rate tester GT7100MI produced by the High Speed ​​Rail Testing Company.

[0368] Weather resistance: Test the weather resistance of high gloss surface according to SAE J2527 standard, evaluate the color difference △E, and the total radiation dose is 2500kJ / m 2 The larger the △E, the worse the weather resistance. It is generally considered that △E ≥ 3 is unqualified.

[0369] Heat deformation temperature: using ISO 75-1A method (flat, load 1.8MPa, heating rate 120℃ / h), sample without annealing treatment, sample thickness 4mm.

[0370] Table 1. Performance test results

[0371]

[0372]

[0373] From the data in Table 1, it can be seen that, compared with Comparative Examples 1-13, while ensuring the weather resistance of the product, Examples 1-3 have significantly improved gloss, higher impact strength, higher melt index, and better heat resistance. This indicates that the present invention significantly improves the gloss and impact strength of the ASA colloid particles while ensuring the weather resistance and heat resistance of the ASA colloid particles through a specific structure, specific components and their proportions, and an optimized preparation method.

[0374] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A high-gloss ASA rubber powder, which is a graft copolymer of acrylic rubber and styrene-acrylonitrile copolymer, and comprises a core layer, a nucleus layer and a shell layer from the inside to the outside; the particle size of the core layer is 50-100nm; the particle size of the high-gloss ASA rubber powder is 100-300nm; The core layer comprises the following components in terms of weight: Butyl acrylate 100-120 parts; 1-5 parts of methylpropionamide; 1-10 parts of composite emulsifier; Initiator 0.1-1 part; Nano silicon dioxide 0.5-1.2 parts; 100-180 parts of water.

2. The high gloss ASA rubber powder according to claim 1, characterized in that: The molecular weight of the high-gloss ASA rubber powder is 400,000-600,000.

3. The high gloss ASA rubber powder according to claim 1, characterized in that: The core layer comprises the following components in terms of weight: Butyl acrylate 90-120 parts; 2.5-5 parts of methylpropionamide; 4-10 parts of composite emulsifier; 5-10 parts of initiator; Nano silicon dioxide 0.8-1.2 parts; 150-180 parts of water.

4. The high gloss ASA rubber powder according to claim 1, characterized in that: The composite emulsifier comprises sodium allyl ether hydroxypropane sulfonate, sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, fatty acid amide and potassium bicarbonate.

5. The high gloss ASA rubber powder according to claim 4, characterized in that: In the composite emulsifier, the mass ratio of sodium allyl ether hydroxypropane sulfonate to sodium 2-propyl ether 3-hydroxypropane-1-sulfonate is 1:0.4-0.

8.

6. The high gloss ASA rubber powder according to claim 4, characterized in that: The composite emulsifier comprises the following components by weight: 10-20 parts of sodium allyl ether hydroxypropane sulfonate, 10-14 parts of sodium 2-propyl ether 3-hydroxypropane-1-sulfonate, 1-2 parts of fatty acid amide and 6-8 parts of potassium bicarbonate.

7. The high gloss ASA rubber powder according to claim 4, characterized in that: The preparation method of the composite emulsifier is as follows: dissolving sodium allyl ether hydroxypropane sulfonate and sodium 2-propyl ether 3-hydroxypropane-1-sulfonate in water, mixing for 20-30 minutes at 20-30°C; adding fatty acid amide and potassium bicarbonate, and continuing to mix for 10-15 minutes to obtain the composite emulsifier.

8. The high gloss ASA rubber powder according to claim 1, characterized in that: The initiator is at least one of persulfate, thiosulfate and bisulfite.

9. The high gloss ASA rubber powder according to claim 8, characterized in that: The initiator is persulfate.

10. The high gloss ASA rubber powder according to claim 9, characterized in that: The initiators are ammonium persulfate and potassium persulfate; the mass ratio of the ammonium persulfate to the potassium persulfate is 1:1-1.

2.

11. The high gloss ASA rubber powder according to claim 1, characterized in that: The core layer, the raw materials, by mass fraction, include the following components: Styrene 15-25 parts; 4-10 parts of acrylonitrile; Composite emulsifier 0.1-1.5 parts; Ethoxy trimethylolpropane triacrylate 0.5-1.2 parts; Initiator 0.1-0.3 parts; Molecular weight regulator 0.05-0.15 parts; 20-40 parts of water.

12. The high gloss ASA rubber powder according to claim 11, characterized in that: The core layer, the raw materials, by mass fraction, include the following components: Styrene 20-25 parts; Acrylonitrile 5-10 parts; Composite emulsifier 0.8-1.2 parts; Ethoxy trimethylolpropane triacrylate 0.5-0.8 parts; Initiator 0.1-0.2 parts; Molecular weight regulator 0.05-0.08 parts; 30-40 parts of water.

13. The high gloss ASA rubber powder according to claim 11, characterized in that: The molecular weight regulator is diisopropyl xanthate disulfide and n-dodecyl; the mass ratio of diisopropyl xanthate disulfide to n-dodecyl is 0.1-0.5:

1.

14. The high gloss ASA rubber powder according to claim 1, characterized in that: The shell layer, the raw materials, by mass fraction, include the following components: 40-60 parts of styrene; 32-45 parts of acrylonitrile; 2-5 parts of methyl methacrylate; Composite emulsifier 0.2-2 parts; Initiator 0.2-1 part; 40-100 parts of water.

15. The high gloss ASA rubber powder according to claim 14, characterized in that: The shell layer, the raw materials, by mass fraction, include the following components: 40-50 parts of styrene; 32-40 parts of acrylonitrile; 3-5 parts of methyl methacrylate; Composite emulsifier 0.8-2 parts; Initiator 0.2-0.8 parts; 60-100 parts of water.

16. The high gloss ASA rubber powder according to claim 1, characterized in that: The mass ratio of the core layer: the core layer: the shell layer is 25-40: 30-35: 30-40.

17. The method for preparing the high gloss ASA rubber powder according to any one of claims 1 to 16, characterized in that: The following steps are involved: S1: mixing butyl acrylate, methyl propionamide, composite emulsifier, initiator, nano-silica and water, and polymerizing to obtain a core layer emulsion; S2: the core layer emulsion is mixed with styrene, acrylonitrile, composite emulsifier, ethoxy trimethylol propane triacrylate, molecular weight regulator and water, and an initiator is added for polymerization to obtain a double-layer structure of a core layer wrapped in a core layer; S3: The double-layer structure of the core layer wrapped in the core layer obtained in S2 is mixed with styrene, acrylonitrile, methyl methacrylate, a composite emulsifier and water, and an initiator is added for polymerization, condensation, aging, dehydration and drying.

18. The preparation method according to claim 17, characterized in that: In S1, the polymerization temperature is 55-65°C; In S2, the polymerization temperature is 60-80°C; In S3, the polymerization temperature is 80-90°C.

Citation Information

Patent Citations

  • A method for preparing high-strength ASA resin for building materials

    CN109897141B

  • Preparation method of ASA resin

    CN113150460A

Cited By

  • High-impact high-gloss ASA resin and preparation method thereof

    CN119798880A